Cartilage oligomeric matrix protein is differentially expressed in human subcutaneous adipose tissue and regulates adipogenesis - Denton, N; Pinnick, K; Karpe, F (Elsevier, 2018)
Objective The composition of the extracellular matrix (ECM) impacts adipocyte function and might determine adipose tissue (AT) function and distribution. Cartilage oligomeric matrix protein (COMP), a matricellular protein usually studied in bone and cartilage, is highly differentially expressed between subcutaneous abdominal and gluteal AT. This study aimed to explore COMP's role in human subcutaneous abdominal and gluteal AT and preadipocyte biology. Methods COMP mRNA levels were measured in whole AT and immortalised preadipocytes via quantitative (q)-PCR. Tissue and cellular COMP protein were measured via Western blot and immunohistochemistry; plasma COMP was measured by ELISA. The effect of COMP on adipogenesis in immortalised preadipocytes was evaluated by qPCR of adipogenic markers and cellular triacylglycerol (TAG) accumulation. Results qPCR analysis of paired subcutaneous abdominal and gluteal AT biopsies (n = 190) across a range of BMI (20.7–45.5 kg/m2) indicated ∼3-fold higher COMP expression in gluteal AT (P = 1.7 × 10−31); protein levels mirrored this. Immunohistochemistry indicated COMP was abundant in gluteal AT ECM and co-localised with collagen-1. AT COMP mRNA levels and circulating COMP protein levels were positively associated with BMI/adiposity but unrelated to AT distribution. COMP expression changed dynamically during adipogenesis (time × depot, P = 0.01). Supplementation of adipogenic medium with exogenous COMP protein (500 ng/ml) increased PPARG2 expression ∼1.5-fold (P = 0.0003) and TAG accumulation ∼1.25-fold in abdominal and gluteal preadipocytes (P = 0.02). Conclusions We confirmed that COMP is an ECM protein which is differentially expressed between subcutaneous abdominal and gluteal AT. Despite its depot-specific expression pattern, however, AT COMP mRNA levels and plasma COMP concentration correlated positively with overall obesity but not body fat distribution. Exogenous COMP enhanced adipogenesis. These data identify COMP as a novel regulator of AT and highlight the importance of the ECM to AT biology.